PENERAPAN BALANCED SCORECARD SERTA ANALISIS SWOT DALAM PERANCANGAN STRATEGI PADA BADAN USAHA MILIK DAERAH PT BANK X - Wahyudi Kukuh; Nimas Aryany Pratiwi; Maria Eliza (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
The Balanced Scorecard analyzes the overall performance of the organization through four perspectives. This study tries to show a Balance Scorecard perspective, then a SWOT analysis and can determine the company's position according to the Internal External Matrix. The object of this research is a holding company in the banking sector. Data collection methods in this study are primary and secondary data. Primary data can be obtained through interviews with key informants, and secondary data is obtained through documentation of the required data obtained from PT Bank X. The matrix is in accordance with the company's SWOT, then the results will be clarified using the IFE Matrix (Strength - Weakness) and EFE Matrix (Opportunities - Threats). The two Matrix that has been formed are plotted into the Internal - External Matrix and are in quadrant 1, so that PT Bank X's strategic position can be found in the Grow and Build position. The most appropriate strategy based on the Grow and Build position is to apply an Intensive Strategy with a specific strategy using market development strategies and product development. Based on the analysis of the BSC and IE Matrix, a strategic recommendation is produced on product development, including making efforts to improve the quality of human resources, improve credit quality, and digitize banking in preparing for competition in the era of industrial revolution 4.0.